Mechanisms of Public Management of the Development of the Road Industry Abroad - Tymokha, Anatoliy (Theory and Practice of Public Administration, 2024)
The article is devoted to a comprehensive study of the mechanisms of public management of road infrastructure development in Germany, the USA, China and Brazil. The relevance of the study is determined by the need to modernize and expand the road network in Ukraine, increase its safety and efficiency. The article analyzes the current state of research in the field of road management and public management of its development, reveals insufficient attention to the issues of adapting foreign experience to Ukrainian realities, in particular, regarding the peculiarities of legislation, institutional capacity and potential risks associated with the implementation of public-private partnerships and concessionsThe purpose of the article is to conduct a comparative analysis of the mechanisms of public management of road infrastructure development in selected countries in order to identify effective practices that can be adapted and implemented in Ukraine.The main material of the article reveals various aspects of public management of road development in the studied countries: organizational and legal mechanisms (degree of centralization and decentralization, legislative framework, technical regulations), financial instruments (budget funds, road funds, PPPs, concessions), strategic planning ( long-term development plans, priority investment directions), project management, quality and safety assurance (high standards, quality control, inspections), as well as stakeholder involvement (public hearings, consultations, surveys).The results of the study allow us to conclude that the choice of specific tools and approaches to public management of road development depends on many factors, including the level of economic development, political system, institutional capacity and geographical features of the country. However, the experience of other countries can provide valuable lessons for Ukraine, contributing to the development of an effective and balanced policy in the field of road management.